Polityczność kwestii światopoglądowych w ujęciu dyskursywnym - Ozimek, Magdalena (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2015)
One of the dimensions of axiological values’ and agendas’ presence in the public sphere is seeing worldview as being political. Due to the nature of the phenomenon of belief as well as the category of politics, proposed consideration of these issues in the analysis of political science may be a discursive approach. Mechanisms which are revealing on the basis of discourse allow to specify categories of naturalization and pragmatism as the two basic types of articulation. As a result, we can identify examples of the implications of this phenomenon that have been identified in the form of SEP (somebody’s else problem) and tensions within the public-private dichotomy.